Determinants of Service consumer's attitudes and Behavioural intentions towards Sharing Economy for Sustainable consumption: An Emerging Market Perspective. Issue 2 (3rd April 2022) - Kaushal, Leena Ajit; Prashar, Anupama
ABSTRACT: Globally, an expansion in the ecological awareness, proliferation of social commerce and advancement of communication technologies have evolved shared economy (SE) as a new way of consumption. Understanding the inherent impulses of SE providers, platforms and users are key to the success of global SE platforms and services aiming to expand in emerging markets. This study employed the lens of Self-Determination theory to examine the motives underlying the participation behavior of SE users in one of the largest emerging market of India. We surveyed the 615 SE service user across four shared service categories, namely, accommodation, rides, coworking spaces, lifestyle goods. The hypotheses on direct and indirect effect were tested using techniques of Structural Equation Modeling. The results show that the intrinsic motive of perceived familiarity and extrinsic motive of economic benefits are the strongest determinant of attitude and continuous use intentions of Indian SE users. Additionally, we found that attitude has a strong positive influence on use intentions of Indian users. Prior SE research on consumer motivations is mostly on Airbnb and Uber data in western settings. This study provides more balanced knowledge about the potential of SE in the emerging markets.